Agricultural Exports, Financial Openness and Ecological Footprints: An Empirical Analysis for Pakistan - Haq, Ihtisham ul; Khan, Dilawar; Taj, Hassan; Allayarov, Piratdin; Abbas, Azeem; Khalid, Muhammad; Awais, Muhammad (International Journal of Energy Economics and Policy, 2021)
The environmental degradation has become one of the most debatable issues in 21st century. The current study explores the impact of agricultural exports and financial openness on ecological footprints in Pakistan. For this purpose, the study utilizes time series data. Unit root tests are applied to check the data for unit root problem and autoregressive distributed lagged (ARDL) model is employed for cointegration analysis. The results of the study show that agriculture exports are responsible for lessening ecological footprints in long run as well as in short run thus; increase in agricultural exports will restrain environmental degradation in Pakistan. The results also revealed that financial openness increases ecological footprints henceforth, environmental degradation in Pakistan. Moreover, trade openness, economic growth and energy consumption are also significant factors of ecological footprints. Keywords: Agricultural exports, financial openness, ecological footprints, Pakistan. JEL Classifications: C22, E01, F18, Q57 DOI: https://doi.org/10.32479/ijeep.11744